Infective Endocarditis due to Unusual Pathogens Complicated with Pulmonary Thromboembolism: A Rare Occurrence in a Premature Infant - Saikat Patra; Prachi Patwal; Chinmay Chetan; Girish Gupta (Wolters Kluwer Medknow Publications, 2024)
Background: Survival of low birth weight preterm neonates has increased with the availability of better neonatal care, however, the use of central lines for longer duration increases the risk of bacterial and fungal sepsis. Neonatal infective endocarditis (IE) is a rare presentation of neonatal sepsis and is often associated with complications and high mortality. Clinical Description: A 36 weeker, premature baby, hospitalized for early onset sepsis, was transferred to our hospital on day 15 of life, with an umbilical catheter in situ, with fever, respiratory distress, and persistent thrombocytopenia. Clinical examination revealed decreased oxygen saturation, crepitations in the right lung field, systolic murmur, and hepatomegaly. Management and Outcome: Baseline investigations revealed positive septic screen with thrombocytopenia with meningitis, neonatal cholestasis, and right sided consolidation on chest X ray. A two dimensional echocardiography (ECHO) revealed vegetation on the tricuspid valve, and blood culture from two sites revealed growth of Candida tropicalis and Serratia marcescens. Colistin, tigecycline, and amphotericin B therapy were initiated as per sensitivity along with low molecular weight heparin for prevention of embolization. The baby developed acute worsening in respiratory distress after 4 weeks of therapy. Repeat ECHO revealed increased size of cardiac vegetation and computed tomography of thorax with pulmonary angiography revealed pulmonary thromboembolism. Unfortunately, the baby succumbed to complications of IE. Conclusion: Invasive instrumentations such as umbilical catheterization and prolonged hospitalizations of premature newborns predispose them to develop IE, especially with unusual organisms. Such infections have a complicated course and may be fatal.